Mechanical properties and microstructure of magnesia–fly ash pastes. Issue 5 (4th July 2019) - Wang, Dongxing; Wang, Hongwei; Di, Shengjie
Abstract : An attempt has been made to develop the alkali-activated industrial by-products to reduce the production of Portland cement in many civil engineering applications. The reactive MgO–fly ash blends were reported to have the potential as a novel material for construction. This paper investigates the strength and hydration reaction of reactive MgO–fly ash blends at room temperature up to 90 days. The variation of compressive strength is studied by taking into account the effect of the amount of MgO, curing time and water to solid ratio. The hydration products are analysed through X-ray diffraction, thermogravimetric analysis, scanning electron microscope and energy-dispersive spectrometer (EDS). The result analysis confirms the formation of cementitious materials including brucite (Mg(OH)2 ) and magnesium silicate hydrate (M-S-H). The amount of M-S-H and brucite is greatly affected by the factors such as MgO content and curing time, and the M-S-H gels are distributed in the form of fibrous or clustered structure. The EDS results reveal that the Mg/Si molar ratio in M-S-H phases alters significantly when the mass ratio of MgO to fly ash varies in pastes. Further study should be performed to investigate the reaction kinetics and hydration products of MgO–SiO2 –H2 O and MgO–Al2 O3 –H2 O systems in reactive MgO–fly ash blends.